THE UK RISK SHARING SCHEME: FINAL 10 YEAR ANALYSIS. Issue 12 (15th November 2016) - Palace, Jacqueline; Duddy, Martin; Bregenzer, Thomas; Piske, Benjamin; Lawton, Michael; Joel, Feng Zhu; Tremlett, Oger Helen; Boggild, Mike; Robertson, Neil; Lilford, Richard; Tilling, Kate; Ben-Shlomo, Yoav; et al.
Abstract : Following guidance from NICE in 2002, the risk-sharing Scheme (RSS) was established to ensure cost-effective provision of interferon-beta and glatiramer acetate in the UK. The aim was to permit price adjustment should prospectively collected disability data deviate from the predicted course of treated patients modelled from natural history data. The 6 year analysis 1 showed a reduced decline in utility of 42% in the RSS cohort against the modelled natural history, in excess of the 38% required to match NICE's target of £36, 000/QALY. In the two models used, a multi-level model and a continuous Markov model, this equated to a reduction in EDSS progression of 40% and 24% respectively. 10 year data collection was completed in July 2015. 97.5% of eligible and treated subjects contribute to the final analysis, with 75.1% having ≥year 9 EDSS scores. The predicted course of the RSS cohort on and off treatment has been modelled to 10 years from baseline values using both methods and compared to the observed data. The calculated deviation scores demonstrate how the drugs have performed in the real world compared to predictions from the short term randomised trials. The results will be presented.